Voltammetric characterisation of the radical anions of 4-nitrophenol, 2-cyanophenol and 4-cyanophenol in N,N-dimethylformamide electrogenerated at gold electrodes - Forryan, C; Lawrence, N; Rees, N; Compton, R (2004)
The electrochemical reductions of 4-nitrophenol, 2-cyanophenol and 4-cyanophenol were studied in N,N-dimethylformamide (DMF) at gold macro- and microdisk electrodes. It was inferred at the gold macroelectrode that the reduction of the parent molecule to the corresponding radical anion is chemically irreversible due to a rapid protonation process in which the basic radical anion reacts with the acidic parent compound. The use of microdisk electrodes and fast scan cyclic voltammetry (144 kVs-1) for the reduction of each of the three compounds of interest failed to outrun the kinetics of the protonation reaction, suggesting a fast process with a second-order rate constant in excess of 1 × 107 M-1 s-1. © 2003 Elsevier B.V. All rights reserved.